Did Proto-Chadic have velar nasals and prenasalised obstruents? - H. Ekkehard Wolff (Afrika und Übersee, 2022)
Ever since the Afroasiatic affiliation of Chadic as a whole was suggested by Joseph H. Greenberg in his seminal re-classification of African languages since the 1950s and has been generally accepted, i.e. encompassing both ‘Chado-Hamitic’ and ‘Chadic’ languages of influential pre-Greenbergian genetic classifications, the issue of whether Proto-Chadic possessed prenasalised obstruents and velar nasals has been repeatedly raised and debated in the literature, yet without final consent. All of the 196 presently known Chadic languages would appear to possess these consonants in their synchronic phonemic inventories. The present article reviews the debate in view of recently available new insights on the historical phonology and lexical reconstruction based on data from 66 of the 79 known Central Chadic languages, i.e. the most numerous and most diverse branch of Chadic. According to these recent comparative studies of Central Chadic that allow to reconstruct Proto-Central Chadic phonology and lexicon, there is massive evidence to show that both velar nasals and prenasalised obstruents emerged as results of natural phonological processes probably already on the proto-language level, but need not be reconstructed for the proto-language’s phonemic inventory. And if Proto-Central Chadic did not have these consonants as inherited phonemes, then this would also be true for its predecessor, Proto-Chadic. The major processes leading to the emergence of velar nasals and prenasalised obstruents were segmental fusion and the emergence of prensalisation prosody that arose from the de-segmentalisation and prosodification of reconstructed nasals. The article summarises the evidence and gives illustrative examples for the reconstructed phonological processes, which created conditioned allophones that eventually became phonologised yielding synchronic phonemes in the modern Central Chadic languages.